Pengaruh Religiusitas Dan Cinta Uang Terhadap Persepsi Etis Mahasiswa Akuntansi - Pattimahu, Angel Merlyn; Hasmawati, Hasmawati; Yesaya, Mey C; Birahy, Denita; de Fretes, Marissa Falyn; Idris, Rafli (Jurnal Akuntansi Manado (JAIM), 2024)
This study aims to test and analyze the effect of religiosity on the ethical thinking of accounting students and to test and analyze the effect of love of money on the ethical perceptions of accounting students. This research is a quantitative study that takes samples from students of the Ambon State Polytechnic focusing on Accounting Department. The sampling technique used is purposive sampling method with the criteria of students who have passed auditing and professional ethics courses. The sample taken amounted to 150 people. The data analysis technique used is multiple regression analysis. The results of this study indicate that Religiosity has a significant effect on ethical perceptions and Love of Money have a significant effect on ethical perceptions of accounting students as well.